Minimally invasive aspiration of thrombi and masses in left-sided cardiac chambers: a comprehensive literature review - Gunga, Ziyad; Rigollot, Augustin; Wolff, Margaux; Meier, David; Eeckhout, Eric; Rancati, Valentina; Ltaief, Zied; Verdugo-Merchese, Mario; Muller, Olivier; Kirsch, Matthias (Frontiers in Cardiovascular Medicine, 2025)
The management of large intracardiac masses, such as thrombi, tumors, or endocarditic vegetations, presents significant challenges due to their friable nature and the risks of embolization or hemodynamic compromise. While surgical removal remains the gold standard, it is often contraindicated in high-risk patients. Minimally invasive techniques, particularly thromboaspiration, offer a promising alternative, especially for left-sided cardiac chambers where systemic circulation and delicate anatomy heighten procedural risks. This review analyzes the evolving role of thromboaspiration for left-sided cardiac masses, focusing on 24 cases from 14 studies published between 2014 and 2024. Most cases utilized the AngioVac® system, with others employing devices such as Lasso®, Occlutech®, and Amplatz® systems. Neuroprotection was implemented in 79% of cases, primarily using Sentinel® devices. Access was predominantly transseptal, though transapical, transcaval, and femoral routes were also utilized. Notably, 88% of procedures were performed without ECMO support. The results highlight a high success rate (92%) in mass removal with minimal complications, although potential publication bias must be acknowledged. This success underscores thromboaspiration's viability not only for patients unfit for surgery but also for those with intracavitary or pedunculated thrombi. Thromboaspiration represents a less invasive, effective solution for managing left-sided cardiac masses, expanding its applicability beyond right-sided cases. This review emphasizes the need for further studies to establish standardized protocols and encourage broader adoption of this innovative technique in clinical practice.